“Como eu vou descer naquele lugar?”: percepções sobre a segregação socioespacial em áreas de vulnerabilidade social do bairro Cascavel Velho em Cascavel/PR - Grande , Franciele Moreira (2021)
Socio-spatial segregation is a common process in Brazilian cities associated with class division and struggle, from which the poorest population tends to reside in peripheral areas with absence of urban infrastructure. For this analysis, the neighborhood of Cascavel Velho in the city of Cascavel-PR were selected, focusing on two areas of social vulnerability: the Mutirão Laice and Settlement Wilson Gonçalves, which were built by different processes of socio-spatial segregation. The first started in the 1970s and the second came in 2016, after the relocation of residents from an expropriated area in the Jardim Gramado neighborhood. This research had as main objective to evaluate the perception of the inhabitants of their areas about the condition of socio-spatial segregation that they experience. The methodology correlated qualitative and quantitative data. The first were produced by semi-structured interviews with residents of the areas analyzed, while the second were socioeconomic indicators about the Cascavel Velho neighborhood obtained from SIDRA / IBGE. The research indicates that precariousness in terms of housing and urban infrastructure is prevalent in both areas. However, residents' perceptions and perspectives are different. In Mutirão Laice, the population presents situations of abandonment, while in the Settlement Wilson Gonçalves, echoing statements related to the struggle for housing and the best days of hope. Currently, there is an ongoing regularization process of the land in both areas, which opens a positive perspective because it gives more security to the investment of the inhabitants in their homes and allows the use of public resources in the infrastructure of the place. Finally, it was identified that socio-spatial segregation in the cases analyzed also occurs on an intraneighborhood scale, based on the stigmas and prejudices in the Cascavel Velho neighborhood regarding the residents of the two areas of social vulnerability analyzed.